(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
One definition of decision making is the act of selecting one or more alternatives from a set thatare deemed desirable enough to be pursued in order to reach a goal or set of objectives. The decisionmakingprocess is quite unpredictable. Therefore, it is essential for a useful decision aid to be able tohandle imprecise and confusing information, such as huge profits, rapid speed, and cheap price.Diversity of thought, perspective, and belief must be honored. A decision model that takes intoconsideration the identification, evaluation, and combination of criteria and alternatives is needed torepresent the decision-making and evaluative processes in a fuzzy situation. Sometimes, we’re facedwith a dilemma that requires us to choose the optimal course of action based on a single factor, such thepotential financial reward or the level of personal danger involved. However, the key to solving mostproblems in the real world is learning to make judgments based on a wide range of information.